ISBS: The evolution of a revolution - Ostarello, J. Z. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The idea of an organization dedicated to the advancement of sports biomechanics germinated during the Montreal Olympic Games in 1976, where the Olympic Biomechanics Cinematography research team, led by Professor Juris Terauds, discussed the issue at length. At the University of Alberta in the fall of 1977 Terauds continued to explore the idea through a long series of philosophical conversations with Geoff Dyson. These discussions explored a variety of topics, including the value of biomechanics in sports, the nature of biomechanics research, and ways in which coaches could be brought "out of the dark ages" and into the starting blocks with scientifically based information. An informal meeting was held in conjunction with the Clinic for High Speed Biomechanics Cinematography in Edmonton, Canada during the International Congress of Sports Sciences in July 1978. Participants expressed a strong sentiment supporting an international society of sports biomechanics. It was not, however, until the following month, at the Commonwealth Games, that the 29 members of the biomechanics cinematography research team addressed the problems of forming and implementing an international society focusing on sports biomechanics. Juris Terauds obtained a two-year sabbatical leave from the University of Alberta for the period 1979 to 1981. He used this time to promote the idea of an international society with biomechanics enthusiasts from around the world. This was no trivial task in an era when the dominant technologies were typewriters, snail mail and non-cell telephones. Nonetheless, he was able to consult with a substantial group of sports scientists. It is interesting that in spite of the relative difficulty of communication, 17 of 40 contributors he contacted were not residents of the U.S.A.